Critical Issues in Indigenous Studies : Multiple InJustices : Indigenous Women, Law, and Political Struggle in Latin America. - Hern?andez Castillo, R. A?ida (Critical issues in indigenous studies., 2016)
Draws together over two decades of research by the author into activism and legal pluralism as practiced and understood by Indigenous women in Latin American countries, analyzing the struggles of indigenous women in Mexico, Guatemala, and Colombia to secure justice and equal rights. The ethnographic approach taken in the book analyzes activism and legal pluralism at the local, state, and international scales and synthesizes the author's experiences interacting with activists at those different levels. The manuscript draws on critical discourse and feminist theories to address the tensions and struggles indigenous women activists face in Latin America.